2021
DOI: 10.21037/atm-21-2570
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-GAS5 promotes spinal cord repair and the inhibition of neuronal apoptosis via the transplantation of 3D printed scaffold loaded with induced pluripotent stem cell-derived neural stem cells

Abstract: Background: Stem cell transplantation has been increasingly used for spinal cord repair, and some achievements have been made. However, limited stem cell sources as well as immune rejection and ethical issues have restricted its wide application. Therefore, to achieve further breakthroughs regarding the application of stem cell transplantation to treat spinal cord injury (SCI), it is important to develop a stem cell line that can effectively avoid immune rejection and ethical issues.Methods: Urine cells (UCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Due to significant therapeutic effects on patients with stroke, stem cell therapy has received extensive attention. Various types of cells (bone marrow mononuclear cells, bone marrow/adipose-derived stem/stromal cells, umbilical cord blood cells, neural stem cells, and olfactory ensheathing cells) have been shown to improve neurological function in animal models of stroke [17]. Therefore, in this study, we also tested some stem cell markers to explore the possible regulatory relationship among curcumin, lncRNA GAS5, and stem cell markers which have never been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Due to significant therapeutic effects on patients with stroke, stem cell therapy has received extensive attention. Various types of cells (bone marrow mononuclear cells, bone marrow/adipose-derived stem/stromal cells, umbilical cord blood cells, neural stem cells, and olfactory ensheathing cells) have been shown to improve neurological function in animal models of stroke [17]. Therefore, in this study, we also tested some stem cell markers to explore the possible regulatory relationship among curcumin, lncRNA GAS5, and stem cell markers which have never been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a Western blot analysis indicated an increase in the expression level of B cell lymphoma/leukemia-2 along with a decrease in the amount of Bcl-2 associated X protein, cytochrome C, and cleaved caspase-3. Morphological observations confirmed that the transplantation of cells could improve renovation in mouse model of SCI, while the restorative effects of the transplantation were inhibited by the growth arrest-specific 5 (GAS5) silencing gene [39].…”
Section: Induced Pluripotent Stem Cells (Ipsc)mentioning
confidence: 72%
“…CircRNA is a newly identified ncRNA, with a stable circular structure. Change in circRNA expression may affect the level of its origin mRNA [ 19 ]. DEG enrichment showed that 1,284 genes changed significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the mRNA analysis results, we focused on ncRNA changes with GV-EA. Previous studies suggested that regulating lncRNA-GAS5 promotes SCI recovery and limits neurocyte apoptosis [ 19 , 20 ]. Our lncRNA results showed that 91 of the overlapping DEGs increased, and 169 decreased, with GV-EA.…”
Section: Discussionmentioning
confidence: 99%